Influences on preschoolers' altruism - Limback, Ellie (2012)
There has been a resurgence of interest in prosocial behaviour in recent years, but many authors avoid the topic of altruism due to the difficulty of discerning the motives behind the behaviour. The present thesis takes a behavioural definition of altruism (i.e. that the point of interest is the altruistic action rather than the underlying motives) and employs a paradigm from experimental economics that minimises the impact of motivating factors aside from altruism: the dictator game. Preschool children's emerging altruistic behaviour is assessed and the norms governing this behaviour are hypothesised. Chapter 1 gives an introduction to prosocial behaviour in general, before focussing on altruism and the dictator game. It demonstrates that while behaviour in older children and adults is influenced by numerous intrinsic and extrinsic factors, little is known about influences on the altruistic and dictator game behaviour of preschool children. Chapter 2 conducts a standard DG with 4-5 year-old children with particular focus on the influence of siblings. It also examines the impact of endowment size, providing a reduced endowment in order to ascertain whether children's understanding of the numerosities involved influences dictator game behaviour. There was no effect of endowment size upon DG behaviour, but sibling status was found to influence donations, with children with older siblings being more likely to donate than those without older siblings. These results are discussed in terms of models of sibling influence. Chapter 3 extends these findings by examining whether adults behave similarly to children and whether the influence of older siblings remains in adulthood. A shift in the influence of siblings was observed, with adults with siblings being more generous than those without siblings, rather than older siblings in particular being beneficial. How these findings further inform models of sibling influence is discussed. Chapter 4 examines how the source of the endowment influences preschoolers' altruistic behaviour in the dictator game by asking children to earn their endowments rather than provide them as a windfall. While previous work has shown that adults are less generous when they have earned their endowment than when it is a windfall, children showed little difference in behaviour according to the source of their endowment, although there is evidence to suggest that children with older siblings are beginning to internalise the relevant norms (otherwise there was no effect of sibling status). Chapter 5 examines the effect of framing upon children's altruistic behaviour by providing different information about the recipient (rather than no information as is standard in the DG). Children gave more to a recipient with positive characteristics than one with negative characteristics and were also influenced by the mere possession of information. Chapter 6 sums up by demonstrating how these findings interact to inform our understanding of preschoolers' altruistic behaviour and outlines areas for future research. Altogether, this thesis demonstrates that there are numerous influences on preschoolers' altruistic behaviour but children are nonetheless similarly altruistic to adults rather than more selfish, as is often assumed.